Supplementation of lake extender with cysteamine preserves quality parameters and fertility potential of post-thawed rooster sperm during cryopreservation process - Reza Masoudi; Saeid Esmaeilkhanian; Maryam Hatami; Mohsen Sharafi; Ali Hatefi; Fatemeh Zarei; Reihaneh Nateghi; Mohammad Reza Tohidkia (BMC Veterinary Research)
Abstract Background In the cryopreservation process, rooster spermatozoa are vastly sensitive to reactive oxygen species (ROS). This study aimed to investigate the effects of Lake extender supplemented via Cysteamine (CYS) on the quality and fertility characteristics of rooster semen during the cryopreservation process. Methods Semen samples were collected from 10 proved Ross-308 roosters, diluted and cryopreserved in the Lake extender which contained 0, 1, 2, 4, and 8 mM of CYS (C-0, C-1, C-2, C-4, and C-8, respectively). Motility parameters, membrane integrity, abnormal morphology, mitochondrial activity, acrosome integrity, viability, apoptosis status, lipid peroxidation, DNA fragmentation, ROS concentration, as well as fertility potential were evaluated after thawing. Results total motility and progressive motility were higher (P ≤ 0.05) in C-1 and C-2 compared to the other groups. The C-1 showed higher (P ≤ 0.05) membrane integrity, mitochondrial activity, acrosome integrity, viability, and lower (P ≤ 0.05) late apoptosis, lipid peroxidation, DNA fragmentation, and ROS concentration compared to the other groups. During fertility evaluation, C-1 presented a higher fertility rate than the control group. In cases of velocity parameters, abnormal morphology, early apoptosis, necrosis, and hatching rate, no significant difference (P > 0.05) was found. Conclusion using the optimal concentration of CYS (1 mM) in the Lake extender is useful for protecting rooster sperm during the cryopreservation process and it could be used for reproductive programs.